(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
This article comprehensively examines the effect of magnesium on the health of pregnant women. The biological importance of magnesium, the increased demand for it during pregnancy, the clinical signs of magnesium deficiency, and its consequences are analyzed scientifically. The article also discusses magnesium-rich foods, diets, and preventive recommendations. It focuses on maintaining magnesium balance during pregnancy to ensure the health of both the mother and the fetus. The research results show that adequate and timely intake of magnesium plays a crucial role in the healthy progression of pregnancy.